2015
DOI: 10.1016/j.jesf.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A hard/heavy intensity is too much: The physiological, affective, and motivational effects (immediately and 6 months post-training) of unsupervised perceptually regulated training

Abstract: The motivational processes associated with RPE 13 regulated exercise (greater competence and autonomy and more positive affect) potentially explain the maintained fitness in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…This finding is consistent with previous research documenting the effects of self-selected vs. imposed intensity on PA (Ekkekakis et al, 2008(Ekkekakis et al, , 2011Hamlyn-Williams et al, 2014;Rose & Parfitt, 2012;VazouEkkekakis & Ekkekakis, 2009) and work suggesting that this "at risk" group may benefit specifically from an affect-based exercise prescription (Ekkekakis & Lind, 2006;Ekkekakis et al, 2010). Moreover, the findings add to the growing body of evidence (Parfitt et al, , 2015Williams et al, 2015) supporting the use of affective factors as a primary method of exercise prescription (Garber et al, 2011). However, the novel finding we report here extends previous research in demonstrating that the positive effect of an affect-guided prescription on PA is specific to those individuals for whom PA is more likely to be experienced as affectively unpleasant (i.e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with previous research documenting the effects of self-selected vs. imposed intensity on PA (Ekkekakis et al, 2008(Ekkekakis et al, , 2011Hamlyn-Williams et al, 2014;Rose & Parfitt, 2012;VazouEkkekakis & Ekkekakis, 2009) and work suggesting that this "at risk" group may benefit specifically from an affect-based exercise prescription (Ekkekakis & Lind, 2006;Ekkekakis et al, 2010). Moreover, the findings add to the growing body of evidence (Parfitt et al, , 2015Williams et al, 2015) supporting the use of affective factors as a primary method of exercise prescription (Garber et al, 2011). However, the novel finding we report here extends previous research in demonstrating that the positive effect of an affect-guided prescription on PA is specific to those individuals for whom PA is more likely to be experienced as affectively unpleasant (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The promising findings from this pilot trial are consistent with similar studies that have shown the benefits of regulating exercise intensity using affect or perceived exertion (Parfitt et al, , 2015Williams et al, 2015) and add to the evidence base supporting the use of affect as a primary mode of exercise prescription. Overall, the study indicated the importance of the way in which PA is prescribed to inactive adults, with particular attention to matching the prescription to the level of CRF of the individual.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the difficulty and complexity of conducting medium-to longterm studies have not facilitated much investigation into adherence to exercise programs. Parfitt [28] verified the 6-month effect on physical fitness and affective responses of sedentary people after an 8-week intervention program. Three groups participated in the training: a control group, a group that exercised in PSE 13 (Borg 06-20), and group in PSE 15.…”
Section: Exercise Intensity and Affective Responsesmentioning
confidence: 86%
“…Performing 30 minutes of moderate-intensity exercise, i.e., 64-76% of maximum heart rate (HR max ) (at least 5 days a week), or 20 minutes of vigorous intensity, i.e., 77-95% of HR max (3 days a week), is the minimum recommendations proposed by the American College of Sports Medicine (ACSM) for health-related physiological benefits (ACSM, 2011). Studies published in recent decades have shown that exercise intensity is also one of the main influencers of affective exercise response [5,[26][27][28].…”
Section: Exercise Intensity and Affective Responsesmentioning
confidence: 99%